Nanosecond pulse fibre laser based on nonlinear polarisation rotation effect. Issue 19 (1st September 2013) - Anyi, C.L.; Haris, H.; Harun, S.W.; Ali, N.M.; Arof, H.
Abstract : A nanosecond pulse erbium‐doped fibre laser (EDFL) is demonstrated based on nonlinear polarisation rotation effect using a highly concentrated EDF in a ring cavity. The EDFL generates a stable multi‐wavelength comb with a constant spacing of 0.22 nm in the 1533.6 nm wavelength region at a pump power of 87.6 mW. A stable mode‐locked operation also commences with a constant repetition rate of 77 MHz with pulse width that varies from 5.3 to 6.8 ns as the pump power is increased from 87.6 to 168.9 mW. With careful adjustment of the polarisation controller, a stable square pulse is obtainable at a pump power of 128.3 mW with a pulse width of 6.5 ns and an average output power of 5.0 mW, which translates to the pulse energy of 35 pJ. The square pulse is generated based on the nonlinear polarisation switching effect inside the laser cavity.